Semantics, systematicity and problems of standardization of the term writing in Ukrainian language education - Turkevych, Oksana (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The terms of Ukrainian language education (in particular, methods of teaching Ukrainian as a foreign language) are part of a professional language that is constantly evolving, absorbing new concepts from world didactics and specifying existing ones. The newly formed microsystems of terms need to be standardized, unified, and mostly harmonized in order to coordinate them with foreign equivalents. All this determines the relevance of the proposed study. The purpose of the article is to analyze the semantic paradigm of the term writing, to distinguish specific terms and describe the concepts they denote, as well as to suggest ways of terminology standardization and harmonization. To achieve this goal, a descriptive method and a method of component analysis were used. Elements of the comparative method were used to compare Ukrainian and foreign equivalents. The term writing in Ukrainian language education denotes a productive type of speech activity. Mastering writing means mastering graphic symbols, being able to use them to capture the idea, and as a result – to develop the ability to create text. In order to standardize the professional language, it is proposed to use a special unit of writing, which naturally complements the system of speech activities: reading, speaking, listening. According to the criterion of «goal», a group of terms is distinguished: academic, practical and creative writing. According to other criteria, different types of writing are systematized (for example, collective, pair, individual; controlled, partially controlled, independent). Often their form is not yet established in the professional language. Thus, the analysis showed the patterns of formation of the paradigm of the term writing on various grounds and revealed problematic moments in the formation of the analyzed system of terms. The proposed terms (the scope of which is defined on the basis of how they function in language education) with an attempt to outline the definition can be the basis for terminology standardization and harmonization.